Nest and brood chamber structure of two south American dung beetles: Gromphas lacordairei Brullé and Ontherus sulcator (Fabricius) (Coleoptera: Scarabaeidae: Scarabaeinae) - Sánchez, María Victoria (2008)
Thirty-three nests of Gromphas lacordairei Brullé and Ontherus sulcator (Fabricius) were studied at Navarro, Buenos Aires, Argentina. Nests examined in the field and micromorphological studies of brood chambers demonstrate for the first time that G. lacordairei shows delayed provisioning, constructs nests with storage burrows, and makes brood masses with a discrete external wall of soil. These characters place G. lacordairei in Pattern II nesting behavior. Ontherus sulcator constructs either brood balls beneath dung pads by direct provisioning or only feeding burrows. The orientation and structure of the egg chamber is different from those of Ontherus mexicanus Harold.